2013
DOI: 10.4049/jimmunol.1202369
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-Derived γδ Regulatory T Cells Suppress Innate and Adaptive Immunity through the Induction of Immunosenescence

Abstract: Fundamentally understanding the suppressive mechanisms utilized by different subsets of tumor-infiltrating regulatory T (Treg) cells is critical for the development of effective strategies for anti-tumor immunotherapy. γδ Treg cells have recently been identified in human diseases including cancer. However, the suppressive mechanisms and functional regulations of this new subset of unconventional Treg cells are largely unknown. In the current studies, we explored the suppressive mechanism(s) utilized by breast … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
188
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 174 publications
(194 citation statements)
references
References 52 publications
6
188
0
Order By: Relevance
“…7 These studies clearly indicate that senescent tumor-infiltrating T cells are dysfunctional and could indirectly amplify and maintain the immunosuppressive effects mediated by tumor cells and Treg cells in the tumor microenvironment. [5][6][7] These results suggest a potential mechanism for the failures seen in multiple clinical trials of tumor vaccines and adoptive T cell therapies. In addition, the possibility of blocking the induction of T cell senescence and restoring the effector function of senescent T cells are critical goals for enhancing antitumor immunity.…”
mentioning
confidence: 89%
See 3 more Smart Citations
“…7 These studies clearly indicate that senescent tumor-infiltrating T cells are dysfunctional and could indirectly amplify and maintain the immunosuppressive effects mediated by tumor cells and Treg cells in the tumor microenvironment. [5][6][7] These results suggest a potential mechanism for the failures seen in multiple clinical trials of tumor vaccines and adoptive T cell therapies. In addition, the possibility of blocking the induction of T cell senescence and restoring the effector function of senescent T cells are critical goals for enhancing antitumor immunity.…”
mentioning
confidence: 89%
“…5,6 In the current study, we further showed that multiple types of tumor cells, including breast cancer, melanoma, colon cancer, prostate cancer, ovarian cancer, and head and neck cancer, can also utilize the same mechanism as Treg cells and directly induce T cell senescence. 7 Senescent T cells develop significant phenotypic alterations, such as permanent loss of CD28 expression, cell cycle arrest, and secret proinflammatory and suppressive cytokines.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…31,32 For example, tumor cells promote gd T cells to adopt a regulatory T cell (Treg) phenotype. Such gd Tregs damp antitumor immunity 33 and contribute to the immunosuppressive microenvironment that is characteristic of most tumor cells. 34 Deficient gd T cell functions have already been observed in various malignancies, including hematological, 20 liver, 35 breast 35 and gastric cancers.…”
Section: Gd T Cells and Cancer Immunitymentioning
confidence: 99%